Application of product information in building maintenance work / Nur Izwani Iberahim - Iberahim, Nur Izwani (2005)
Maintenance is the last stage in building life cycle which is applied to ensure that the building can function and fulfill the need of occupants in the building. Generally, maintenance is any works that apply to the building components or elements to avoid any breakdown or repair any damages. A good maintenance is actually depends on a good management. How the management of the maintenance work function usually planned at the early stage of the building life. The failure to plan a good maintenance is actually the failure to the maintenance. One factor to the building failures is the users of the building where the daily activity usually is the main causes of this failure. Whether they know it or not, generally the building elements will age after few years of usage by the users. This is because each element has life duration and it needs a replacement after the duration expired or not functions anymore.